2019
DOI: 10.3390/ijerph16245124
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Residents among Rural Communities with Medical Group Practice in Japan

Abstract: Elucidating the perceptions of residents regarding medical group practice (GP) among rural communities (GP-R) in Japan will be useful for establishing this system in such communities. A survey by questionnaire, as made by experts in rural health, was conducted in 2017. The self-administered questionnaire inquired about the perceptions of residents for accepting the GP-R into the community’s healthcare using seven major elements of GP-R. The questionnaire was randomly distributed to 400 adult residents who live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Second, some studies found that although digital visits showed promise, face-to-face visits were still preferred [33,34,38]. Third, in five studies [38,39,[52][53][54], the clinicians concluded that digital visits are better suited for certain needs than others. All of this highlights the need for further development based on the patients' needs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, some studies found that although digital visits showed promise, face-to-face visits were still preferred [33,34,38]. Third, in five studies [38,39,[52][53][54], the clinicians concluded that digital visits are better suited for certain needs than others. All of this highlights the need for further development based on the patients' needs.…”
Section: Discussionmentioning
confidence: 99%
“…Another five studies described a service targeted at users with infrequent healthcare service needs. These needs included minor infections, such as sinusitis, urinary tract infection, or lower respiratory tract infections [50,51], low-acuity illnesses [52], and pregnancy or recent childbirth [35]. The solution studied by Alam et al [35] included synchronous communication, as well as the possibility of a phone call.…”
Section: 92023mentioning
confidence: 99%
“…Otherwise, the insulin pump introduction has several limitations, including healthcare access for frequent outpatient visits, mainly in early-stage for accustoming mechanical troubles and economic problems in the countries where CSII is self-funded [4]. Rural people in Japan have many difficulties with healthcare access because Japan is a mountain-or island-rich country, and approximately 10% of the population lives in hardto-move areas [5]. Therefore, they could not attend to outpatients frequently and felt demotivated to introduce CSII by their circumstances.…”
Section: Introductionmentioning
confidence: 99%